ALGUNOS ALCANCES PARA EL ESTUDIO DE ARTESANÍA EN CUERO SOME NOTES ON LEATHER HANDCRAFT IN PERU - Miranda Castillo, Estela (2006)
The history ofPeruvian popular art needs to be completed with a referenceto works in leather. Trunks, petacas and coffers have a historie and artisticmeaning. The article shows the different ways in which leather hasbeen wrought, the tools used and the objects produced all along different stages in Peruvian history. It also informs about leather preservation andcuration.